Senjata Kaum Lemah: Perlawanan Sehari-Hari Petambak Garam - Yety Rochwulaningsih (Jurnal Sejarah Citra Lekha, 2016)
This article examines how the salt farmer’s weapon in their resistance against the life’s oppressive conditions and why this resistance model lead in their everyday life that tipically vulnerable helpless in many ways. It is studied with using of historical method that emphasizes on oral history. For collecting data and observation purposes, it is equipped with qualitative analysis. The results showed that the Indonesian salt farmers, especially in Java has a quirk resistance, which tends to be soft, closed, and not frontal, but it continuously takes place in their productive activity daily rhythm. It is taken because they do not have bargaining power with other parties both in economic, social, cultural and political.